Physical activity based interventions for reducing body mass index in children aged 6–12 years: a systematic review - Muñoz-Urtubia, Nicolás; Vega-Muñoz, Alejandro; Salazar-Sepúlveda, Guido; García-Gordillo, Miguel Ángel; Carmelo-Adsuar, José (Frontiers in Pediatrics, 2025)
IntroductionThis systematic review aimed to examine the impact of physical activity-based interventions on body mass index (BMI) reduction in children aged 6–12 years.MethodsA comprehensive search was conducted in the PubMed database following PRISMA guidelines and using the PICOS framework. A total of 13,927 records were retrieved, of which seven studies met the inclusion criteria. Methodological quality was assessed using the Mixed Methods Appraisal Tool (MMAT).ResultsIncluded studies comprised both preventive and treatment-oriented interventions that aimed to reduce BMI through physical activity. Interventions that integrated family and school components, and were grounded in behavioral theories such as Self-Determination Theory and Social Cognitive Theory, showed greater effectiveness in reducing BMI and improving body composition.DiscussionMultilevel strategies that enhance autonomy, competence, and social support within biopsychosocial frameworks appeared to improve motivation and adherence. Although BMI z-score reductions were modest, they reached clinically meaningful thresholds. These findings support the implementation of context-sensitive, comprehensive strategies involving families, schools, and communities to promote healthy behaviors and sustainable outcomes in pediatric populations.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, PROSPERO CRD42024547428.